HYDROBIOLOGICAL STATUS OF A LESSER IDMALAYAN RIVER - Mohan, Madan (Journal of Indian Fisheries Association, 2015)
It is generally observed that a variety of physical and chemical variableshave considerable impact on the biological life in a mountain river whichinclude plankton, benthic algae, benthic invertebrate and finally the fisheryresources. They are often subjected to extreme hydrological disturbancesparticularly during rainy seasons when increased volume of water create'Wash Off" situation for existing fauna and flora. A case study of a lesserHimalayan river - the Gaula which drains the south-central part of Kumaonregion in Uttaranchal is presented here. Since this river does not get snowmeltwater, it mainly depends on steady flow of the groundwater round theyear. The climate of the area is characterized with long winters, short summerand good amount of rain during monsoon months. The infiltrated groundwaterwhich seeps into the surface soil layers during monsoon seasons is the chiefsource of discharge of water during winter and summer season.Keywords: Hydrobiology, flora and fauna, Himalayan river